Pengaruh Peresapan Air Hujan Menggunakan Lubang Resapan Biopori (LRB) - Ashri Febrina Rahmasari; Suripin Suripin; Sudarno Sudarno (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2015)
The increasing of quantity and quality of community needs recipitation change the late of land use from green land which function is as water filtration and to make organic compost in LRB as water conservation and handling waste as well. This study is done by making LRB application. Filtration application is taken continues in every 60 minutes and periodic by used by used bucket and organic natural decomposition. Compost used was taken from kitchen waste, leaf litter and mixed of both of them. The density of compost varied from 0,5 kg, 2 kg, and 3 kg per hole. The observation was done in 14 weeks. Infiltration of LRB increased from the first week to nineth week and then decreased until the end of observation (fourteenth week) due to the soil pore had been recharged of water. Maximum infiltrationof LRB with 3 kg of kitchen waste then filtration of LRB with 2 kg og starfruits leaf litter and LRB with 0,5 kg of mixed waste. Infiltration rate for the first maximum were 274,79 l/h, 250,18 l/h, and 239,4 l/h. The effect of LRB was calculated based in the LRB capacity of one LRB can contained of 0,2 ;/d household waste during 20 days with 10 weeks cycle.